IMPLEMENTASI PAJAK PERTAMBAHAN NILAI (PPN) ATAS PENGADAAN BARANG/JASA DALAM PERSPEKTIF UU NO. 7 TAHUN 2021 DI RUMAH SAKIT JIWA DAERAH DR. ARIF ZAINUDIN SURAKARTA - Rifatun Maulani; Suprihati Suprihati; Desy Nur Pratiwi (CV. Denasya Smart Publisher, 2024)
This study aims to analyze the implementation of Value Added Tax (VAT) on the procurement of goods/services at the dr. Arif Zainudin Regional Psychiatric Hospital in Surakarta from the perspective of Law No. 7 of 2021. The research method used is qualitative with a descriptive approach. Data were obtained through in-depth interviews and observations related to the procurement of goods/services and VAT reporting at the psychiatric hospital. The results of the study indicate that the implementation of VAT on the procurement of goods/services at the dr. Arif Zainudin Regional Psychiatric Hospital in Surakarta has been carried out well in accordance with the applicable laws, namely Law No. 42 of 2009 with a VAT rate of 10% and Law No. 7 of 2021 with a VAT rate of 11%. The procurement process and VAT reporting are conducted systematically and structurally, although in 2022 there were obstacles in the form of delayed VAT reporting which caused the institution to pay late penalties. The increase in the VAT rate has impacted the procurement costs and the fulfillment of medical needs. Overall, the implementation of VAT at the dr. Arif Zainudin Regional Psychiatric Hospital in Surakarta has complied with the prevailing regulations and demonstrates a commitment to tax compliance.